Bery Engebretsen letter to Carl J. Bendorf regarding fall bird sightings, December 1, 1987 - Engebretsen, Beryet al (1987)
Letter from Bery Engebretsen to Carl J. Bendorf regarding fall bird sightings, December 1, 1987. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed